(Overcoming) Maternity Bias in the Workplace: A Systematic Review - Arena, David F.; Volpone, Sabrina D.; Jones, Kristen P. (Journal of Management, 2023)
Maternity, a period of transition beginning with prenatal bodily changes and progressing through postnatal lactation, is experienced by up to 66% of working women. Over the past several decades, research on maternity in the workplace has grown exponentially to reveal salient maternity biases that plague women as they navigate their employee and motherhood identities. With the aim of providing information that aids scholars and practitioners in better understanding the experiences of working mothers, we conducted a systematic review of 239 papers on maternity bias (i.e., formal, interpersonal, and internalized). Our interdisciplinary review discusses these three forms of bias and how they might present across different career stages for working mothers. Additionally, we review the antecedents that may drive maternity bias and the outcomes that result for working mothers who perceive or anticipate bias at work. Finally, we discuss areas of previous research aimed at overcoming maternity bias from the perspective of working mothers, their colleagues, and their organization. We conclude by discussing the trends brought to light in our review, the collective strengths and weaknesses of commonly adopted theoretical perspectives of the research reviewed, implications for combating maternity bias for women and their organizations, and recommendations for future research. Our model of maternity bias comprehensively reviews past work to provide insights into the bias that working mothers endure at work but also provides a path forward, as better understanding these biases empower organizations, coworkers, and employees to remediate maternity bias.